TECHNOLOGICAL FEATURES OF COMBINED DEVELOPMENT OF UPHORNY DEPOSITS - Tadzhiev Sh. T; Kobilov O.S; Tukhtashev A. B; Mustafoev I. G (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, in the basis of the analysis of sources, the technological features of openunderground mining of upland deposits are revealed. The main factors influencing the effectiveness of open-underground mining have been determined, which will need to be taken into account when making design decisions to determine the boundaries of open-underground works.